Eggshell Based Nano-Engineered Hydroxyapatite and Poly(lactic) Acid Electrospun Fibers as Potential Tissue Scaffold - Vitus A. Apalangya; Vijaya K. Rangari; Boniface J. Tiimob; Shaik Jeelani; Temesgen Samuel (International Journal of Biomaterials)
Nanocomposite electrospun fibers were fabricated from poly(lactic) acid (PLA) and needle-like hydroxyapatite nanoparticles made from eggshells. The X-ray diffraction spectrum and the scanning electron micrograph showed that the hydroxyapatite particles are highly crystalline and are needle-liked in shape with diameters between 10 and 20 nm and lengths ranging from 100 to 200 nm. The microstructural, thermal, and mechanical properties of the electrospun fibers were characterized using scanning electron microscope (SEM), thermogravimetric analysis (TGA), dynamic scanning calorimetry (DSC), and tensile testing techniques. The SEM study showed that both pristine and PLA/EnHA fibers surfaces exhibited numerous pores and rough edges suitable for cell attachment. The presence of the rod-liked EnHA particles was found to increase thermal and mechanical properties of PLA fibers relative to pristine PLA fibers. The confocal optical images showed that osteoblast cells were found to attach on dense pristine PLA and PLA/HA-10 wt% fibers after 48 hours of incubation. The stained confocal optical images indicated the secretion of cytoplasmic extension linking adjoining nuclei after 96 hours of incubation. These findings showed that eggshell based nanohydroxyapatite and poly(lactic acid) fibers could be potential scaffold for tissue regeneration.